Role of vitamin D receptor in the antiproliferative effects of calcitriol in tumor-derived endothelial cells and tumor angiogenesis in vivo - Chung, I.; Hang, G.Z.; Seshadri, M.; Gillard, B.M.; Yu, W.D.; Foster, B.A.; Trump, D.L.; Johnson, C.S. (2009)
Calcitriol (1,25-dihydroxycholecalciferol), the major active form of vitamin D, is antiproliferative in tumor cells and tumor-derived endothelial cells (TDEC). These actions of calcitriol are mediated at least in part by vitamin D receptor (VDR), which is expressed in many tissues including endothelial cells. To investigate the role of VDR in calcitriol effects on tumor vasculature, we established TRAMP-2 tumors subcutaneously into either VDR wild-type (WT) or knockout (KO) mice. Within 30 days post-inoculation, tumors in KO mice were larger than those in WT (P < 0.001). TDEC from WT expressed VDR and were able to transactivate a reporter gene whereas TDEC from KO mice were not. Treatment with calcitriol resulted in growth inhibition in TDEC expressing VDR. However, TDEC from KO mice were relatively resistant, suggesting that calcitriol-mediated growth inhibition on TDEC is VDR-dependent. Further analysis of the TRAMP-C2 tumor sections revealed that the vessels in KO mice were enlarged and had less pericyte coverage compared with WT (P < 0.001). Contrast-enhanced magnetic resonance imaging showed an increase in vascular volume of TRAMP tumors grown in VDR KO mice compared with WT mice (P < 0.001) and FITC-dextran permeability assay suggested a higher extent of vascular leakage in tumors from KO mice. Using ELISA and Western blot analysis, there was an increase of hypoxia-inducible factor-lot, vascular endothelial growth factor, angiopoietin :1, and platelet-derived growth factor-BB levels observed in tumors from KO mice. These results indicate that calcitriol-mediated antiproliferative effects on TDEC are VDR-dependent and loss of VDR can lead to abnormal tumor angiogenesis. Cancer Res 2009;69(3):967-75